Customary land utilization arrangements for the construction of micro hydro power plants in West Sumatra - Yunita, Masna; Mirwati, Yulia; Warman, Kurnia; Fendri, Azmi (Edelweiss Applied Science and Technology, 2025)
This research investigates the legal framework governing the use of traditional land for the development of small-scale hydroelectric power generation in West Sumatra. The construction of PLTMH is prioritized in remote areas that have not been reached by PLN. In the process of constructing the MHP, land use is required. However, the location planned for the development is on customary land owned by indigenous people. For the Minangkabau people, the use of customary land has its own rules; on the other hand, there are national legal rules about land, electricity, and investment laws. Data was collected through a normative legal research approach, which is a research method that relies on the study of applicable legal norms. The main focus of this approach is to examine legal materials as the main data source, especially laws and regulations relevant to the research topic, such as regulations that apply nationally and regulations that apply at the regional level, especially in the West Sumatra region.